Solid organ transplantation after hematopoietic stem cell transplantation in childhood: A multicentric retrospective survey - Faraci, Maura; Bertaina, Alice; Dalissier, Arnaud; Ifversen, Marianne; Schulz, Ansgar; Gennery, Andrew; Burkhardt, Birgit; Badell Serra, Isabel; Diaz-de-Heredia, Cristina; Lanino, Edoardo; Lankester, Arjan C; Gruhn, Bernd; et al. (American journal of transplantation, 2019)
We report data obtained from a retrospective multicenter pediatric survey on behalf of the European Society for Blood and Marrow Transplantation (EBMT). Information on solid organ transplantation (SOT) performed in pediatric recipients of either autologous or allogeneic hematopoietic stem cell transplantation (HSCT) between 1984 and 2016 was collected in 20 pediatric EBMT Centers (25.6%). Overall, we evaluated data on 44 SOTs following HSCT including 20 liver (LTx), 12 lung (LuTx), 6 heart (HTx), and 6 kidney (KTx) transplantations. The indication for SOT was organ failure related to intractable graft-vs-host disease in 16 children (36.3%), acute or chronic HSCT-related toxicity in 18 (40.9%), and organ dysfunction related to the underlying disease in 10 (22.8%). The median follow-up was 10.9 years (95% confidence interval: 1.7-29.5). The overall survival rate at 1 and 5 years after SOT was 85.7% and 80.4%, respectively: it was 74% and 63.2% after LTx, 83.2% after HTx, and 100% equally after LuTx and KTx. This multicenter survey confirms that SOT represents a promising option in children with severe organ failure occurring after HSCT. Additional studies are needed to further establish the effectiveness of SOT after HSCT and to better understand the mechanism underlying this encouraging success.
Keywords: transplantace jater; proporcionální rizikové modely; Proportional Hazards Models; Organ Transplantation; Lung Transplantation; transplantace plic; Retrospective Studies; pediatrics; kojenec; transplantace ledvin; Europe; mladiství; Cohort Studies; výsledek terapie; Evropa; transplantace orgánů; průzkumy a dotazníky; bone marrow/hematopoietic stem cell transplantation; mužské pohlaví; Heart Transplantation; Infant; nemoc štěpu proti hostiteli; míra přežití; kohortové studie; dítě; Child; Child, Preschool; Allografts; Hematopoietic Stem Cell Transplantation; ženské pohlaví; graft-vs-host disease (GVHD); Kidney Transplantation; transplantace hematopoetických kmenových buněk; retrospektivní studie; předškolní dítě; Autografts; Graft vs Host Disease; Humans; clinical research/practice; Liver Transplantation; Survival Rate; Surveys and Questionnaires; lung (allograft) function/dysfunction; organ transplantation in general; alografty; kidney failure/injury; heart failure/injury; liver disease; autologní štěp; Female; Adolescent; Treatment Outcome; transplantace srdce; lidé; Male